Becoming ecological citizens: connecting people through performance art, food matter and practices. (October 2016) - Roe, Emma; Buser, Michael
Engaging the interest of Western citizens in the complex food connections that shape theirs' and others' personal wellbeing around issues such as food security and access is challenging. This article is critical of the food marketplace as the site for informing consumer behaviour and argues instead for arts-based participatory activities to support the performance of ecological citizens in non-commercial spaces. Following the ongoing methodological and conceptual fascination with performance, matter and practice in cultural food studies, we outline what the ecological citizen, formed through food's agentive potential, does and could do. This is an ecological citizen, defined not in its traditional relation to the state but rather to the world of humans and non-humans whose lives are materially interconnected through nourishment. The article draws on the theories of Berlant, Latour, Bennett and Massumi. Our methodology is a collaborative arts-led research project that explored and juxtaposed diverse food practices with artist Paul Hurley, researchers, community partners, volunteers and participants in Bristol, UK. It centred on a 10-day exhibition where visitors were exposed to a series of interactive explorations with and about food. Our experience leads us to outline two steps for enacting ecological citizenship. The first step is to facilitate sensory experiences that enable the agential qualities of foodstuffs to shape knowledge making. The second is to create a space where people can perform, or relate differently, in unusual manners to food. Through participating in the project and visiting the exhibition, people were invited to respond not only as 'ethical consumers' but also as 'ecological citizens'. This participatory approach to research can contribute to understandings of human-world entanglements.